Labor Force Dynamics of Older Married Couples - Blau, David M. (Journal of Labor Economics, 1998)
This article analyzes the dynamics of joint labor force behavior of older couples in the United States. Using the Retirement History Survey (RHS) I analyze the determinants of joint retirement and the effect of one spouse's labor force status on the labor force transitions of the other spouse. The results reveal strong associations between the labor force transition probabilities of one spouse and the labor force status of the other spouse. These result from structural differences in exit and entry behavior by the spouse's status. Several lagged endogenous variables have substantial effects on behavior even after controlling for unobserved heterogeneity.